Amelioration of Cerebral Vasospasm and Secondary Injury by Vigabatrin After Experimental Subarachnoid Hemorrhage in the Rabbit - (:unkn) unknown (ELSEVIER SCIENCE INC, 2020)
BACKGROUND: Vigabatrin, an antiepileptic drug, increases the level of gamma aminobutyric acid in the brain by inhibiting its catabolism. Because gamma aminobutyric acid has been proved to have vasodilatory effects, in the present study, we investigated the effect of vigabatrin to treat experimental subarachnoid hemorrhage (SAH)-induced vasospasm. METHODS: A total of 30 New Zealand white rabbits were divided into 3 groups of 10 each: the control group, SAH group, and vigabatrin group. Experimental SAH was established by injection of autologous arterial blood into the cisterna magna. In the vigabatrin group, the rabbits were administered vigabatrin for 3 days after induction of the SAH. The first dose of vigabatrin was given 2 hours after SAH induction. A daily dose of 500 mg/kg vigabatrin was administered intraperitoneatly. After 3 days, the rabbits were sacrificed, and the brains were removed, together with the cerebellum and brainstem. The basilar artery wall thickness and lumen areas were measured. The neuronal degeneration in the hippocampus (CA1, CA3, and dentate gyrus) was also evaluated. RESULTS: The arterial wall thickness of the vigabatrin group was less than that in the SAH group (P < 0.001), and the mean luminal area of the vigabatrin group was greater than that in the SAH group (P < 0.001). Additionally, the hippocampal neuronal degeneration score of the vigabatrin group was lower than that of the SAH group (P < 0.001). CONCLUSION: These findings have indicated that vigabatrin has a vasodilatory effect in an experimental SAH model in the rabbit. Moreover, it showed a neuroprotective effect in the hippocampal neurons against secondary injury induced by SAH.
Keywords: Subarachnoid hemorrhage; Vasospasm; Vigabatrin; BRAIN-INJURY; BLOOD-FLOW; VASODILATION